REINTERPRETASI PENDAPA PADA DESAIN INTERIOR THIRD SPACE SEBAGAI FASILITAS KOMUNITAS MENUJU SOLO KOTA KREATIF - Dhian Lestari Hastuti; Cahyono Budi Santosa (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Surakarta is one of initiators of Indonesia Creative Cities Network (ICCN), which takes important role in the establishment of Creative Cities in Indonesia. It required synergy among penta helix academician, businessmen/ladies, government, people and media to produce creative ecosystem. While Surakarta community is the center of the implementation and program implementation and creative economic development program within the pattern of interaction, connection and collaboration of five (5) elements above mentioned. In order to create the pattern, it required informal and formal space to facilitate creative activity for community members. In urban community this space named Third Space which is a new space typology after a home and work place. In Javanese community the function of this space provided by pendapa. Pendapa has been long time to function as a place for social interaction between the host and its neighborhood. This article is a result of artistic research which shows reinterpretation of immaterial value of pendapa into architecture and Third Space interior design. Design method based on user need and three various research methodologies, namely scenario based survey, co-creation session and focused interview. Philosophy, socio-culture, function and ergonomic approaches were used as a base to redesign pendapa. It achieves “meeting tree” or kayon, a two (2) floors building with Indisch sytle, Scandinavian interior design. The process and Third Space design produce synergy embodiment between academician and community to support Solo, A Creative City program.